Bentuk Ketidakadilan Gender pada Tokoh Ni Luh Sekar dalam Novel Tarian Bumi Karya Oka Rusmini - Marselina, Selly (Universitas Islam Sumatera Utara, 2025)
This study examines the forms of gender injustice experienced by the character Ni Luh Sekar in the novel Tarian Bumi by Oka Rusmini. The novel, set in Balinese society, portrays a deeply entrenched patriarchal culture that dictates women's roles and limits their autonomy. The research aims to analyze how gender-based discrimination is reflected through the character’s experiences within the sociocultural system, particularly in relation to caste, marriage, and identity. Using a descriptive qualitative method and feminist literary criticism as an analytical framework, the study explores the structural and symbolic oppression embedded in the narrative. The findings reveal that Ni Luh Sekar is subjected to systemic injustice, including marginalization, loss of agency, and internalized oppression, stemming from both cultural traditions and familial expectations. The novel illustrates how these gender biases perpetuate social inequality and silence women’s voices. Ultimately, the research argues that Tarian Bumi serves not only as a literary portrayal of personal struggle but also as a critique of the broader sociopolitical mechanisms that sustain gender injustice. This study contributes to the discourse on gender and literature by highlighting how fictional narratives can expose and challenge real-world inequities.